Dual energy method of material recognition in high energy introscopy systems - Novikov, V.L.; Ogorodnikov, S.A.; Petrunin, V.I. (Вопросы атомной науки и техники, 1999)
Element analysis based on so-called dual energy method is widely used throughout the world in X-ray customs inspection systems for luggage control in airports. It facilitates the routine work of customs officer on identification of illegal drugs and explosives hidden in luggage. Due to the absorption rate difference in material of X-rays generated by sources with different energies, discrimination of materials becomes possible. So the scanned image of inspected object can be represented in physical palette where materials are coloured according to their atomic number.